Wereldkeuken : Chili, Mexico, Brazilië - De Meyer, Lieve; Maestri, Mario; de la Cruz, Patricia; de la Fuentes, Antonio
"Lieve De Meyer; Mario Maestri; Patricia de la Cruz; Antonio de la Fuentes... et al. Oorspronkelijke titel : Cuisine du Monde verschenen bij CNCD"